Pengembangan Modul Ajar Pendidikan Agama Islam dalam Kurikulum Merdeka: Kajian Konseptual tentang Komponen, Prosedur, dan Prinsip Pengembangannya - M Masruni; Hilmi Mizani; Syaiful Bahri Djamarah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This article discusses the development of teaching modules as instructional tools in the implementation of the Merdeka Curriculum. Teaching modules are a transformation of lesson plans, known as Rencana Pelaksanaan Pembelajaran (RPP), which function not only as administrative documents but also as flexible, contextual, and student-centered learning guides. This article uses a library research method by examining and analyzing various relevant written sources, including books, journal articles, educational regulations, and previous research findings. The findings show that teaching modules have several characteristics, namely self-instructional, self-contained, stand-alone, adaptive, and user-friendly. In addition, teaching modules consist of general information, core components, and appendices. Effective teaching module development should consider diagnostic assessment, student characteristics, the Pancasila Student Profile, and the principles of being essential, engaging, meaningful, challenging, relevant, contextual, and continuous. Therefore, teaching modules serve as important instruments for teachers in designing innovative, differentiated, meaningful learning that meets students’ needs.